Pengembangan Bahan Ajar Fisika Berbasis Kontekstual Berbantuan Liveworksheet Untuk Meningkatkan Penguasaan Konsep Kesetimbangan dan Dinamika Rotasi - Azifa, Itsna Nur; Nugroho, Sunyoto Eko (UPEJ Unnes Physics Education Journal, 2023)
Mastery of concepts is very important for students because it is an indicator that students fully understand what has been taught. Based on the results of observations at MAN 2 Brebes, students' mastery of physics concepts was still low. The purpose of this research is to develop physics teaching materials that can improve the mastery of the concept of equilibrium and rotational dynamics. This research is research and development (RnD) with a development model adapted from Borg and Gall, which consists of; (1) research and data collection, (2) planning, (3) preparation and development of teaching materials, (4) validity test of experts/experts, (5) first revision of teaching materials, (6) test of legibility of teaching materials, (7) the second revision of teaching materials, (8) testing the use of teaching materials, (9) refinement. The use of teaching materials was tested using the One Group Pretest-Posttest Design experiment. The subjects in this study were class XI MIPA 3 MAN 2 Brebes. The results of the feasibility test for teaching materials obtained a percentage of 83.86% which indicated the criteria for